2019
DOI: 10.18388/abp.2019_2876
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a single and double biotinylation of xanthohumol on its anticancer activity

Abstract: Two biotinylated derivatives of the main hop chalcone xanthohumol (1) were prepared by a one-step synthesis via esterification using biotin and 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC×HCl) and 4-dimethylaminopyridine (DMAP) as coupling reagents. The products were characterized spectroscopically and their antiproliferative activity toward MCF-7, MCF-10A, HepG2, MDA-MB-231, 4T1 and Balb/3T3 cell lines was investigated using the SRB assay. For all three tested compounds the best activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…In the human organism, they exert numerous beneficial health effects. The best known are anticancer, antioxidant, antiinflammatory, antiviral, antidiabetic, antimutagenic and antimicrobial ones [1][2][3][4][5][6]. Some of these compounds were also characterised as exerting beneficial physiological effects.…”
Section: Introductionmentioning
confidence: 99%
“…In the human organism, they exert numerous beneficial health effects. The best known are anticancer, antioxidant, antiinflammatory, antiviral, antidiabetic, antimutagenic and antimicrobial ones [1][2][3][4][5][6]. Some of these compounds were also characterised as exerting beneficial physiological effects.…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported the synthesis of two biotinylated derivatives of XN prepared through esterification and its anti‐cancer activity was analyzed in different cancer cell lines. The highest efficacy was observed in MCF‐7 and 4T1 breast cancer cells and the analogue compound with double biotinylated XN (Figure 1j) showed highest activity in MCF‐7 and 4T1 breast cancer cells and HepG2 liver cancer cells, followed by the efficacy of other analogue, 4‐ O ‐biotinyl XN (Figure 1k) and original compound XN 62 . Thus, XN and its analogues are effective compounds against cancer and the modification of the structure of XN paves the way to improve the efficacy of the compound in the prevention and treatment of cancer.…”
Section: Analogues Of Xnmentioning
confidence: 99%
“…Source, structure, and analogues of Xanthohumol. (a) Humulus lupulus plant (Photograph by: Craig Chandler, University Communication) ( https://cropwatch.unl.edu), (b) Xanthohumol, (c) Analogue 13n 58 ; (d) Compound 11 59 ; (e) Compound 12 59 ; (f) Naringenin 60 ; (g) Chalconaringenin 60 ; (h) 4‐hydroxy‐4′‐methoxychalcone 60 ; (i) Compound number 13 (with para‐methoxy and fluorine groups on B ring) 61 ; (j) Double biotinylated XN 62 ; (k) 4‐ O ‐biotinyl XN 62 …”
Section: Introductionmentioning
confidence: 99%
“…Natural compounds, including polyphenols with an isoprenyl group, due to their high potential for medical use, nowadays play an important role in the development of new molecularly targeted drugs, dietary supplements or antimicrobial agents [ 27 ]. Along with the development of biological therapeutic methods, these substances started to be used as standards or as substrates to obtain new derivatives [ 28 ].…”
Section: Biological Effects Of Morusin and Its Derivativesmentioning
confidence: 99%